PENGARUH PENGGUNAAN MEDIA KARTU BERGAMBAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Novria Wandira; pramudi yanti; rini marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
One of the life skills that need to be developed through a process of education is critical thinking skills, but in MAN 1 (Model) Bandar Lampung, critical thinking skills students have not developed optimally. This study aimed to determine the influence of illustrated cards media through Team Assisted Individualization (TAI) learning model towards the increase of students' critical thinking skills.This study was a quasi-experimental study with a pretest-posttest design in non-equivalent groups. The research samples were class X4 and X5, selected from the population in accordance with cluster random sampling. The data of this study in the form of quantitative and qualitative data. Quantitative data was obtained from the average value of pretest and posttest, were statistically analyzed by t-test with SPSS version 17 at the level of 95%. Qualitative data in the form of descriptions of students' critical thinking skills, students’ activity data and students’ responses to the use of illustrated card media through TAI learning model that analyzed descriptively. The results showed students' critical thinking skills in experimental class as a whole or for each indicator has increased (pretest = 0.84; posttest = 42.79, N-gain = 0.42). The average percentage of students’ activity in experiments class also showed improvement in all aspects. In addition, all students gave positive responses to the use of illustrated card media through TAI learning model. Thus, learning to use the illustrated card media through learning model TAI influential on the increase of students' critical thinking skills. Keywords: Protist, illustrated card media, TAI learning model, critical thinking skills.